OPTIMIZATION OF AMYLASE PRODUCTION BY BACILLUS AMYLOLIQUEFACIENS USING POTATO PEEL POWDER - Mol. S, Reena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The current study was conducted to improve the production of amylase using Bacillus amyloliquefaciens using both traditional and statistical methods. A central composite design with 20 experiments was utilized to optimize three independent variables, which were selected using the one factor at a time (OFAT) method, to achieve maximum amylase production. The chosen factors, when utilized with this statistical optimization method, demonstrated 3 times increases in amylase production, in comparison to the OFAT technique. The analysis of variance (ANOVA) indicated a high coefficient of determination (R2) and was statistically significant (p < 0.05). The three-dimensional response graph revealed an interdependent interaction among the key variables.